PENGARUH MODEL THINK TALK WRITE TERHADAP KEMAMPUAN MENULIS KEMBALI TEKS BIOGRAFI SISWA KELAS X SMAN 1 KOTO XI TARUSAN - Rahma Putri; Rahayu Fitri; Upit Yulianti DN (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2023)
This study aims to reveal the effect of the Think Talk Write Model on the Ability to Rewrite Biographical Texts of Class X Students of SMA Negeri 1 Koto XI Tarusan. This type of research is pre-experimental, with a one-group pretest-posttest design. The sample class studied was one class without a comparison class which was taken through a purposive sampling technique. The sample class in this study was class X MIPA 4. The research instrument used was to rewrite pretest and posttest biographical texts. The results showed that the ability to rewrite biographical texts for class X students of SMA Negeri 1 Koto XI Tarusan increased before and after using the Think Talk Write model. The average value of the posttest results for the sample class is greater than the average pretest results, namely 71.76 for the posttest and 27.25 for the pretest. Using the results obtained from the posttests on the Ability to Rewrite Biographical Texts of Class X Students at SMA Negeri 1 Koto XI Tarusan, it was concluded that the students were capable of rewriting biographical texts after using the Think Talk Write Model.